Multithreaded programming in structural and object-oriented languages - Wiśniewski, Mateusz (Journal of Computer Sciences Institute, 2019)
The article presents multithreaded programming in selected programming languages such as: C structural and C ++ object oriented approach using Posix Threads libraries for C language and Boost library for C ++ language. The characteristics of selected libraries are also described. Examples of typical programming problems using threads are presented. An effort was made to answer the question of what to do when choosing a language for learning multithread programming and programming in the general meaning of this word.